2018
DOI: 10.5327/z1679443520180167
|View full text |Cite
|
Sign up to set email alerts
|

Afastamentos do trabalho por transtornos mentais: um estudo de caso com servidores públicos em uma instituição de ensino no Ceará, Brasil

Abstract: ARTIGO ORIGINAL RESUMO | Contexto:Os objetivos desse estudo foram descrever os afastamentos do trabalho por transtornos mentais entre servidores públicos para apresentá-los à gestão, pretendendo adotar medidas que colaborassem com a diminuição do absenteísmo. Métodos: Foram avaliados os registros de afastamento por transtornos mentais no período de janeiro a dezembro de 2016, em uma instituição pública de ensino do Estado do Ceará. Os dados foram obtidos por meio da plataforma SIASS (Subsistema Integrado de At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
27

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 13 publications
2
8
0
27
Order By: Relevance
“…The educational level of the position also had an inverse association with the number of workdays lost. This confirms the findings of other studies, national and international, with state servants, who concluded that the absenteeism -illness is higher in individuals with positions with lower remuneration and with the requirement of less schooling, especially in the education sector (SANTI & CHEADE, 2018;LEÃO et al, 2015;LEMOS et al, 2018;BASTOS et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The educational level of the position also had an inverse association with the number of workdays lost. This confirms the findings of other studies, national and international, with state servants, who concluded that the absenteeism -illness is higher in individuals with positions with lower remuneration and with the requirement of less schooling, especially in the education sector (SANTI & CHEADE, 2018;LEÃO et al, 2015;LEMOS et al, 2018;BASTOS et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Alarming data on suicide appear in some of the studies: technical-administrative servers of a federal institution of higher education that had a mood disorder, anxiety disorders and depression reported having had suicidal ideas or have attempted suicide, motivated by the organization of work (BASTOS et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Já na abordagem qualitativa, busca-se na literatura aprofundar a discussão dos dados, considerando a complexidade do fenômeno transtornos mentais. Dessa forma, acredita-se que, ao unir as duas abordagens, valorizam-se ambas, uma vez que uma foi utilizada para complementar a outra (MINAYO, 1993 (BASTOS, et al, 2018).…”
Section: Metodologiaunclassified
“…Uma das áreas afetadas é a do ensino público, onde as consequências com os afastamentos do trabalhador são vivenciadas diretamente na sociedade, tanto na falta do professor na sala de aula, influenciando o aprendizado e desempenho dos discentes (Miranda;Araujo;Marcelino, 2017), quanto na ausência dos servidores que realizam funções de apoio às atividades de ensino Reis Neto;Leite, 2019;Bastos;Saraiva, 2016).…”
Section: Introductionunclassified